THE EFFECT OF SCRIPTED SONGS AS A TEACHING TECHNIQUE ON ENGLISH COMPETENCE OF 4th GRADE STUDENTS OF PRIMARY SCHOOL IN SD SARASWATI TABANAN IN ACADEMIC YEAR 2013/2014 - ., I Gede Putu Adhitya Prayoga; ., Dra.Ni Made Ratminingsih, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menyelidiki pengaruh dari lagu kreasi sebagai sebuah teknik mengajar terhadap kompetensi bahasa Inggris siswa kelas 4 SD Saraswati Tabanan tahun akademik 2013/2014. Post-test only control group design digunakan sebagai desain penelitian. Populasi dari penelitian ini adalah seluruh siswa kelas 4. Melalui teknik Cluster Random Sampling, dua kelas diambil sebagai sampel di penelitian ini, yakni kelas 4B and 4C. Kelas 4B dipilih sebagai kelompok kontrol, sedangkan kelas 4C sebagai kelompok eksperimen. Secara keseluruhan, terdapat 75 siswa terpilih sebagai wakil dari populasi. Siswa di kelompok eksperimen diajarkan dengan menggunakan lagu kreasi, sedangkan kelompok kontrol diajarkan dengan menggunakan teknik konvensional. Di akhir pengajaran, kedua kelompok diberikan post-test. Hasil post-test lalu dianalisis secara deskriptif dan inferensial. Berdasarkan hasil analisis data, ditemukan siswa yang diajar menggunakan lagu kreasi memperoleh hasil yang lebih baik ketimbang mereka yang diajar menggunakan teknik konvensional. Ini dibuktikan dari nilai rerata kelompok eksperiment adalah 79,05, sedangkan kelompok kontrol adalah 69,5. Lebih lanjut, hasil dari independen sampel T-test menunjukan t observed (tobs) adalah 5.000. Hasil ini lebih tinggi dari nilai t critical value (tcv) adalah 1.99 (Î±= 0.05). Ini membuktikan bahwa ada pengaruh signifikan pada kompetensi bahasa inggris antara kelompok eksperimen dan kontrol. Kata Kunci : lagu kreasi, kompetensi bahasa inggris This study aimed at investigating the effect of Scripted Songs as a teaching technique on English competence of the fourth grade students of primary school in SD Saraswati Tabanan in academic year 2013/2014. Posttest only control group design was used as a research design. The population was all the fourth grade students. Through Cluster Random Sampling technique, two classes were taken as the samples in this study, namely class 4B and 4C. Class 4B was assigned as the control group while class 4C as the experimental group. In total, seventy five students were taken as representative of the population. The students in experimental group were taught by using Scripted Songs, while the students in control group were taught by using Conventional Technique. At the end of treatment, both groups were given a posttest. The result of the posttest was then analyzed descriptively and inferentially. Based on the result of data analysis, it was found that the students who were taught by using Scripted Songs obtained better result than those who were taught by using Conventional Technique. It was proven by the mean score of the experimental group was 79.05, while the control group was 69.5. Moreover, the result of the independent sample t-test showed that the value of t observed (tobs) was 5.000. It was higher than the value of t critical value (tcv) was 1.99 (Î±= 0.05). This proved that there was a significant effect on English competence between experimental and control group.keyword : scripted songs, english competence